Réponses

2014-01-20T16:33:18+01:00
A) x-4 = 0
A) x = 4 

D) 4x = 6
D) 4x/4 = 6/4
D) x = 3/2

F) 10x - 2 = 0
F) 10x = 2
F) 10x/10 = 2/10 
F) x = 1/5

G) 4-7b = 2b+ 11
G) -9b = 7
G) -9b/9 = 7/9
G) -b = 7/9
G) b = 7/9

2014-01-20T16:35:26+01:00



a) x-4=0
x=4

b)-4y+3=-5
-4y=-5-3
-4y=-8
y=-8/-4
y=2

c)8y-3=5(2y-3)+6
8y-3=5*2y+5*(-3)+6
8y-3=10y-15+6
8y-10y=-15+6+3
-2y=-6
y=-6/-2
y=3

d)4x=6
x=6/4
x=1.5

e)3x+7=-2x-8
3x+2x=-8-7
5x=-15
x=-15/5
x=-3

f)10x-2=0
10x=2
x=2/10
x=0.2

g)4-7b=2b+11
-7b-2b=11-4
-9b=7
b=7/-9
b=-7/9

h)3(2x-4)=9-3(x-5)
3*2x+3*(-4)=9-3*x-3*(-5)
6x-12=9-3x+15
6x+3x=9+15+12
9x=36
x=36/9
x=4